Development of the Tools to Assess the Impact of Cluster Policy on the Increase in the Competitiveness of Enterprise Structures in the Region - SOLODILOVA, Nataliya Zinov'yevna; IBRAGIMOVA, Nuriya Urstyamovna; KAZYKHANOV, Ruslan Radikovich; ARAPOV, Vasiliy Vladimirovich (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
Substantial transformations occur in the sectoral markets and in corporate relations. New industry structures and markets are forming, the roles and the number of companies and other entities of the markets are redistributed, cluster forms of management come to the fore of economic development of the territories. Given the high degree of imbalance between economic opportunities and social obligations of regions, the development of the business climate is one of the priorities of the regional authorities, and this work should always be the focus of attention of administrations of subjects of the Russian Federation. Therefore, to give an adequate assessment of the currently existing mechanisms for cooperation of the government, business and society, as well as state of the government support for entrepreneurship and its effectiveness, including cluster policy, it is necessary to assess how the general logic of social and economic development of the region matches the internal needs and expectations of the business. The tools to assess the impact of cluster policy on the increase in the competitiveness in the region are suggested in this work. It is important to see and to take into account that the cluster approach provides several advantages: firstly, for the regional government, secondly, for the regional business, and thirdly, for the cluster members. In the formation and development of the cluster, contributions should be assessed and the interests of each member of the cluster should be taken into account. The availability of resources resulting from the wisely conducted cluster policy should increase, and the efficiency of their application in business should improve on the way of the regional economy clustering.